2023
DOI: 10.3390/buildings13071738
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Flexural–Torsional Performance of Thin-Walled Open-Ended Steel Vertical Pile Foundations Subjected to Lateral Loads

Abstract: This research investigates the effects of torsional moments on the mechanical behavior of thin-walled open-ended vertical pile foundations subjected to lateral wind loads. The aim of this research is to determine and quantify the errors using traditional design methods and provide more effective alternatives. The warping and torsion effect generated over the piles due to the resultant lateral load impact outside the shear center is analyzed in field tests. Complementarily, a two-dimensional finite element mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…This observation underscores the pivotal role of the widening sections in determining the load-bearing capacity of piles. Further research [8][9][10][11] indicates a 35-45% increase in the static load resistance of widened piles compared to their non-widened counterparts. In some numerical studies [12], this beneficial effect has been shown to reach as high as 68%.…”
Section: Introductionmentioning
confidence: 99%
“…This observation underscores the pivotal role of the widening sections in determining the load-bearing capacity of piles. Further research [8][9][10][11] indicates a 35-45% increase in the static load resistance of widened piles compared to their non-widened counterparts. In some numerical studies [12], this beneficial effect has been shown to reach as high as 68%.…”
Section: Introductionmentioning
confidence: 99%